Manajemen Pendidikan Islam dalam Perspektif Literatur Akademik - Nadia Nabila; Muhammad Husni (Jurnal Manajemen dan Ilmu Administrasi, 2026)
This study aims to analyze the concept of Islamic educational management, its managerial functions, and its implementation in Islamic educational institutions from the perspective of academic literature. Islamic educational management is one of the essential aspects in managing Islamic educational institutions to achieve educational goals effectively and efficiently based on Islamic values. This library research employed a qualitative descriptive approach. The data sources consisted of various books, scientific journals, academic articles, and related studies. Data collection was conducted through documentation studies and literature reviews, while content analysis was used for data analysis. The study reveals that Islamic educational management is a method of managing educational institutions that not only focuses on administrative aspects but also integrates spiritual principles, trustworthiness (amanah), responsibility, justice, and deliberation (musyawarah) into the educational process. The primary functions of Islamic educational management include planning, organizing, actuating, and controlling. When implemented in Islamic educational institutions, these functions can improve the quality of educational management and shape students with noble character (akhlaq al-karimah). Therefore, Islamic educational management must continue to be developed professionally and adaptively in order to address the challenges of education in the modern era.